Fostering Teacher’s Digital Competencies And Innovative Work Behavior In Facing Merdeka Belajar Policy: Digital Informal Learning As A Mediator - Lutfi Astuti, Kurnia; Ikhwan Setiawan, Ahmad (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
Digital competence is the important issue of education where information technology is growing rapidly through computer networks and online media. The challenge of digitalization is the basis for teachers to develop their digital skills. The Merdeka Belajar Policy is a strategy towards a future education system to adapt on those issues. This study purposes to examine the mediators of digital informal learning between teachers' digital competencies and innovative work behavior. The sampling technique used purposive sampling with criteria of samples that teachers who have taught virtually. The number of samples are 175 teachers. Data analysis in this study used second-order construct of SEM PLS with model repeated indicator approach. The result shows that the teacher's digital competencies significantly influence on digital informal learning and innovative work behavior. The indirect effect gets the result that digital informal learning partially mediates between teacher’s digital competencies and innovative work behavior. The contribution of this research is to provide an overview of current education about the importance of teachers adapting to the digitalization so they can develop innovative work behaviors in teaching and learning.